Prespektif Hukum Ekonomi Islam Tentang Sistem Afiliasi Pada Marketplace Shopee - Sulthonuddin, Bung Hijaj; Rahayu, Nuri (STAI Al Musaddadiyah Garut, 2024)
In this digital era, people are starting to look for income through the Shopee Affiliate Program. However, it also creates doubts because there are commissions coming in from products that are not promoted. The purpose of this research is to find out the mechanisms and perspectives of Islamic economic law regarding the affiliate system in the Shopee marketplace, including the commissions earned by affiliates. Using qualitative methods, namely data collection techniques which will later be analyzed and then conclusions drawn. Based on the research results, it was found that the affiliate system mechanism in the Shopee marketplace according to Islamic law is similar to the ju'alah contract. The affiliate system in the Shopee marketplace is permitted under Islamic law and the commission earned by affiliates is halal. Keywords: Islamic Economic Law, Affiliate System, Shopee Affiliate Program, Shopee Marketplace